Glycerol-3-phosphate dehydrogenase expression and oxygen consumption in liver mitochondria of female and male rats with chronic alteration of thyroid status - Rauchová, H; Mrácek, T; Novák, P; Vokurková, M; Soukup, T (Hormone and metabolic research, 2011)
In our chronic experiments (over several months), the activity and protein amount of glycerol-3-phosphate dehydrogenase (GPDH) in mitochondria isolated from the liver of adult male and female inbred Lewis strain euthyroid (EU), hyperthyroid (TH), and hypothyroid (HY) rats were analyzed by biochemical and Western blot methods. The TH status was induced by intraperitoneal injections of 3,3',5-triiodo- L-thyronine and the HY status with 0.05% solution of methimazole in drinking water. The TH status led to a significant increase and the HY status to a significant decrease of enzyme activity and protein amount in both male and female animals. These changes were, however, more pronounced in females. The EU and TH female rats also showed a significantly higher activity and the TH female rats showed also a significantly higher enzyme amount in comparison with males, while the HY rats showed low levels in both sexes. The glycerol-3-phosphate-dependent oxygen consumption of freshly isolated rat liver mitochondria from the TH animals was higher in comparison with the EU animals and it was activated by idebenone, a synthetic analogue of coenzyme Q, in both the EU and TH rats. Measurements of serum thyroid hormone levels and analysis of anatomical parameters (relative heart and thyroid gland weights) confirmed that our procedures inducing the TH and HY states are efficient and reliable and that determination of GPDH can serve as an additional criterion for the evaluation of the thyroid hormone status.
Keywords: Rats; Glycerolphosphate Dehydrogenase; hypertyreóza; hypotyreóza; Mitochondria, Liver; spotřeba kyslíku; Oxygen Consumption; Disease Models, Animal; hormony štítné žlázy; jaterní mitochondrie; mužské pohlaví; Thyroid Hormones; krysa rodu Rattus; glycerolfosfátdehydrogenasa; modely nemocí na zvířatech; ženské pohlaví; Gene Expression; zvířata; Humans; Hypothyroidism; potkani inbrední LEW; Hyperthyroidism; Rats, Inbred Lew; exprese genu; Female; lidé; Male; Animals